KLASTERISASI UNTUK MENENTUKAN JARINGAN DISTRIBUSI BAWANG MERAH DI PROVINSI JAWA BARAT - Chandra Alpiansyah; Wilmar Putra; Muchamad Fauzi (Jurnal Bayesian : Jurnal Ilmiah Statistika dan Ekonometrika, 2022)
Shallots (Allium cepa L. Aggregatum group) is a type of plant that is used as a spice in various cuisines of Southeast Asia and the world. This plant is thought to have come from Central Asia and Southeast Asia. The high demand and need for shallots have an impact on this commodity, which provides benefits to be cultivated according to the projection of shallot consumption in 2021 in Indonesia reaching 2.8 to 3.8 kg/capita/year. Low production capacity causes traders to have to bring in from outside the city to outside the province. Based on the survey results, shallot traders in the province of West Java are supplied from the central point of distributors in Central Jakarta. This study aims to determine whether the distribution network requires a distribution center point by considering the clustering of distribution distances. The method used to determine the distribution network is K-Means in cluster division and Center of Gravity in determining distribution points. With this method, it can be concluded that with a total of 4 clusters, the results obtained in cluster 1 there are 2 cities, cluster 2 there are 11 cities/districts, cluster 3 there are 12 cities/districts, cluster 3 there are 12 cities/districts, and cluster 4 there are 2 districts is not recommended to create a new distribution center point in each cluster because, the total costs will be higher. So each cluster will receive shallot distribution from the distribution center point in Central Jakarta